The neverending story [videorecording (Blu-Ray)] - Petersen, Wolfgang; Weigel, Herman; Gunn, Moses, 1929-1993; McRaney, Gerald; Hathaway, Noah; Oliver, Barret; Ende, Michael ([Publisher not identified], 2014)
When young Bastian borrows a mysterious, ornately-bound book, he never dreamed turning a page would draw him into a shimmering fantasy world of racing snails, hang-glider bats, soaring luckdragons, puckish elves, a childlike Empress, the brave warrior Atreyu and a slab-faced walking quarry called a Rock Biter.